A review of the main drivers and variability of Central America’s Climate and seasonal forecast systems - Maldonado, Tito; Alfaro, Eric J.; Hidalgo, Hugo G. (Revista de Biología Tropical, 2018)
Central America is a region susceptible to natural disasters and climate change. We reviewed the literature on the main atmospheric and oceanographic forces and climate modulators affecting Central America, for different spatial and time scales. We also reviewed the reported correlation between climate variability, natural hazards and climate change aspects (in the past and future). In addition, we examined the current state of seasonal prediction systems being applied to the region. At inter-annual scales, El Niño/Southern Oscillation is the main climate modulator; however, other indices such as the Tropical North Atlantic, Atlantic Multi-Decadal Oscillation and Pacific Decadal Oscillation, have shown a correlation with precipitation anomalies in the region. Current seasonal forecast systems in the region have shown a constant development, including incorporation of different approaches ranging from statistical to dynamical downscaling, improving prediction of variables such as precipitation. Many studies have revealed the need of including –in addition to the climatic information– socio-economic variables to assess the impact of natural disasters and climate change in the region. These studies highlight the importance of socio-economic and human life losses associated with the impacts caused by natural hazards for organizations and governments. Rev. Biol. Trop. 66(Suppl. 1): S153-S175. Epub 2018 April 01.